Distribution characteristics of low molecular weight organic acids in seawater of the Changjiang Estuary and its adjacent East China Sea: Implications for regional environmental conditions. (December 2020) - Lyu, Lina; Fang, Kejing; Jin, Hong; Yang, Gui-Peng; Liang, Haorui; Ding, Haibing
Abstract: In this study, components, concentrations, distribution characteristics and sources of low molecular weight organic acids (LMWOAs) in seawater of the Changjiang Estuary and its adjacent East China Sea were investigated in March 2015. Lactic, acetic and formic acids were identified with their concentration range of 0–16.7, 0–42.7 and 0–6.7 μmol·L −1, respectively. In the surface seawater, high concentrations of LMWOAs appeared in the sea area close to the estuary and along the coast. LMWOAs were important fractions of dissolved organic carbon and acetic acid was dominant component of LMWOAs. Riverine, terrestrial input, phytoplankton and sediment release were important sources for the LMWOAs, and human activities were considered as dominant sources for them in sampling period. The consistency of regions with high concentrations of LMWOAs, eutrophication, seasonal hypoxia and frequent red tide occurrence suggested LMWOAs as potential indicators for evaluating pollution status in coastal areas. Highlights: Lactic, acetic and formic acids were detected in this study. LMWOAs were significant fraction of dissolved organic carbon. Human activities were the dominant sources for LMWOAs. LMWOAs can be used for evaluating organic pollution status of coastal area.